Respuesta :
Answer:
x has 2 values: [tex]x_{1}=3 + \sqrt{26} *i[/tex] , [tex]x_{2} = 3 - \sqrt{26}*i[/tex]
Step-by-step explanation:
First: Rearrange the equation to get 0 as a result.
(In this case: [tex]x^{2} -6x + 42-7 = 0[/tex]
that can be reduced to: [tex]x^{2} -6x+35=0[/tex])
Second: Apply the quadratic equation formula [tex]x = \frac{-b±\sqrt{b^{2}-4*a*c }}{2*a}[/tex]
For a= 1 ; b= -6 ; c= 35.
Third: Replace & solve to find [tex]x_{1}[/tex] and [tex]x_{2}[/tex] :
[tex]\frac{6±\sqrt{-104}}{2*1}[/tex] (Note: [tex]\sqrt{-104} = 2*\sqrt{-26}[/tex])
And replacing [tex]\sqrt{-1} = i[/tex]:
[tex]x_{1} = 3+\sqrt{26}*i[/tex] and [tex]x_{2} = 3-\sqrt{26}*i[/tex]
Note: If a character  appears, just ignore it (it is an error in the insertion of the formulas, it has no effect on the results)
Answer:
The possible values of x are 3±√26i
Step-by-step explanation:
Given the equation, 7 + 6x = 42 +x², to find the value of x that makes the expression true, we need to rearrange the expression and factorize the resulting equation.
Rearranging:
7 + 6x = 42 +x²
Moving 7+6x to the other side we have:
x²+42-6x-7 = 0
x²-6x+35 =0.
Using the general formula
x = -b±√b²-4ac/2a
From the quadratic function, a = 1, b= -6, c=35
x = 6±√(-6)²-4(1)(35)/2(1)
x = 6±√36-140/2
x = 6±√-104/2
x = (6±√104×-1)/2
x = 6±√104i/2
x = 6±2√26i/2
x = 3±√26i
Note that √-1 = I (a complex value)